Answer:
(a) ![5 * (2x - 1) = 10x - 5](https://tex.z-dn.net/?f=5%20%2A%20%282x%20-%201%29%20%3D%2010x%20-%205)
(b) ![6 * x = x + 2x + 3x](https://tex.z-dn.net/?f=6%20%2A%20x%20%3D%20x%20%2B%202x%20%2B%203x)
(c) ![\frac{1}{2}(x - 6) = \frac{1}{2}x - 3](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%28x%20-%206%29%20%3D%20%5Cfrac%7B1%7D%7B2%7Dx%20-%203)
(d) ![y(3x + 4z) = 3xy + 4yz](https://tex.z-dn.net/?f=y%283x%20%2B%204z%29%20%3D%203xy%20%2B%204yz)
(e) ![z(2xy - 3y + 4x) = 2xyz - 3yz + 4xz](https://tex.z-dn.net/?f=z%282xy%20-%203y%20%2B%204x%29%20%3D%202xyz%20-%203yz%20%2B%204xz)
Step-by-step explanation:
Solving (a):
Given
![10x - 5](https://tex.z-dn.net/?f=10x%20-%205)
Required
Express as a product
Express 10x as 5 * 2x
![10x - 5 = 5 * 2x - 5](https://tex.z-dn.net/?f=10x%20-%205%20%3D%205%20%2A%202x%20-%205)
Apply distributive property
![10x - 5 = 5(2x - 1)](https://tex.z-dn.net/?f=10x%20-%205%20%3D%205%282x%20-%201%29)
![10x - 5 = 5 * (2x - 1)](https://tex.z-dn.net/?f=10x%20-%205%20%3D%205%20%2A%20%282x%20-%201%29)
So:
![5 * (2x - 1) = 10x - 5](https://tex.z-dn.net/?f=5%20%2A%20%282x%20-%201%29%20%3D%2010x%20-%205)
Solving (b):
Given
![x + 2x + 3x](https://tex.z-dn.net/?f=x%20%2B%202x%20%2B%203x)
Required
Express as a product
Express 2x and 3x as 2 * x and 3 * x, respectively
![x + 2x + 3x = x + 2*x + 3*x](https://tex.z-dn.net/?f=x%20%2B%202x%20%2B%203x%20%3D%20x%20%2B%202%2Ax%20%2B%203%2Ax)
Apply distributive property
![x + 2x + 3x = x(1 + 2 + 3)](https://tex.z-dn.net/?f=x%20%2B%202x%20%2B%203x%20%3D%20x%281%20%2B%202%20%2B%203%29)
![x + 2x + 3x = x(6)](https://tex.z-dn.net/?f=x%20%2B%202x%20%2B%203x%20%3D%20x%286%29)
![x + 2x + 3x = 6*x](https://tex.z-dn.net/?f=x%20%2B%202x%20%2B%203x%20%3D%206%2Ax)
So:
![6 * x = x + 2x + 3x](https://tex.z-dn.net/?f=6%20%2A%20x%20%3D%20x%20%2B%202x%20%2B%203x)
Solving (c):
Given
![\frac{1}{2}(x - 6)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%28x%20-%206%29)
Required
Express as a sum/difference
Apply distributive property
![\frac{1}{2}(x - 6) = \frac{1}{2}x - \frac{1}{2}*6](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%28x%20-%206%29%20%3D%20%5Cfrac%7B1%7D%7B2%7Dx%20-%20%5Cfrac%7B1%7D%7B2%7D%2A6)
![\frac{1}{2}(x - 6) = \frac{1}{2}x - \frac{6}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%28x%20-%206%29%20%3D%20%5Cfrac%7B1%7D%7B2%7Dx%20-%20%5Cfrac%7B6%7D%7B2%7D)
![\frac{1}{2}(x - 6) = \frac{1}{2}x - 3](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%28x%20-%206%29%20%3D%20%5Cfrac%7B1%7D%7B2%7Dx%20-%203)
Solving (d):
Given
![y(3x + 4z)](https://tex.z-dn.net/?f=y%283x%20%2B%204z%29)
Required
Express as a sum/difference
Apply distributive property
![y(3x + 4z) = 3x * y + 4z * y](https://tex.z-dn.net/?f=y%283x%20%2B%204z%29%20%3D%203x%20%2A%20y%20%2B%204z%20%2A%20y)
![y(3x + 4z) = 3xy + 4yz](https://tex.z-dn.net/?f=y%283x%20%2B%204z%29%20%3D%203xy%20%2B%204yz)
Solving (e):
Given
![2xyz - 3yz + 4xz](https://tex.z-dn.net/?f=2xyz%20-%203yz%20%2B%204xz)
Required
Express as a product
Factorize
![2xyz - 3yz + 4xz = 2xy * z - 3y * z + 4x * z](https://tex.z-dn.net/?f=2xyz%20-%203yz%20%2B%204xz%20%3D%202xy%20%2A%20z%20-%203y%20%2A%20z%20%2B%204x%20%2A%20z)
Apply distributive property
![2xyz - 3yz + 4xz = z(2xy - 3y + 4x)](https://tex.z-dn.net/?f=2xyz%20-%203yz%20%2B%204xz%20%3D%20z%282xy%20-%203y%20%2B%204x%29)
So:
![z(2xy - 3y + 4x) = 2xyz - 3yz + 4xz](https://tex.z-dn.net/?f=z%282xy%20-%203y%20%2B%204x%29%20%3D%202xyz%20-%203yz%20%2B%204xz)